Beschäftigungsentwicklung und Dynamik des betrieblichen Ausbildungsangebotes. Eine Analyse für den Zeitraum 1999 bis 2008 - Klaus Troltsch; Günter Walden (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
– Since the mid-1990s of the last century, changes in the German apprenticeship system have mainly been discussed under the light of too low participation and training rates of companies. Statistical analysis of relevant questions mostly relies on means derived from cross-sectional data such as the training rate of companies. However, this approach only gives information about companies' training provision at a certain point in time and tells little about the dynamics of company participation in training. Even with overall training rates remaining constant, large shifts in the training participation of certain groups of companies and in the composition of the overall population of training companies may occur. Over time, economic dynamics should also lead to changes in training behaviour. Taking this into account the paper analyses the turnover of apprenticeship places over time. The question is addressed, in which way the supply of training places is influenced by relevant factors mainly concerning changes in companies' human capital. The paper finally assesses the relative importance of policy instruments and unobserved variables compared to economic dynamics.
Keywords: J30; J60; 330; Ausbildungsplatzangebot - Determinanten; betriebliche Berufsausbildung; Ausbildungsinvestitionen; Kosten-Nutzen-Analyse; Ausbildungsbereitschaft; Beschäftigtenstruktur